Tree Shading Effect on Diversity and Competitions of Understorey Cover in IPB Campus Dramaga - Rahmawati, Ilma; Bramasta, Dwika; Ramadhanty, Pramesty Wulan; Susanto, Slamet Arif (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Knowledge of competition at the plant community level is useful as a basis for studying competition aspects in a broader scope. One of the simplest things is understory competition due to differences in tree canopy cover. The purpose of this study was to describe the role of shade trees on competition and understory community structure. A total of 6 plots measuring 1 m × 1 m were made under stands of Ficus calosa, Ficus benjamina, and Terminalia catappa trees (Location 1 and Location 2), while 3 other plots of the same size were made under stands of Hevea brasiliensis trees (Location 3). Structure, composition and diversity were studied using vegetation analysis techniques. The results showed that Locations 1 and 2 were dominated by Phytolacca americana and Asystasia gangetica, while Location 3 was dominated by Axonopus compressus and Asystasia gangetica. Further analysis showed outlier data from the three locations indicated an abundant number of individuals of Phytolacca americana and Asystasia gangetica, and Axonopus compressus. All of these dominant species are invasive. Regression analysis shows that the projection of increasing canopy cover causes an increase in the density of certain species, but not significantly (P >0.05). The higher the dominance index, the smaller the species diversity value. Therefore, it can be concluded that a dominant species is usually competitive and can change the distribution structure and diversity of understory plants under different tree canopies.